Establishment of reference values for prothrombin time, activated partial thromboplastin time and fibrinogen in adults in Burkina Faso - Nebie, Koumpingnin; Sawadogo, Salam; Traore, Catherine; Koulidiati, Jerome; Kima, Donatien; Ouedraogo, Florence Alida Wendyam; Minoungou, Myriam Wendkuni Nikiema; Sawadogo, Salifo; Toure, Awa Oumar; Kafando, Eleonore (Annales de biologie clinique (Paris), 2023)
The ordering of clinical haemostasis tests is increasing in Burkina Faso due to the newly emergence of cardiovascular and metabolic diseases. However, appropriate local reference values (RV) are lacking. Our study aimed to establish RV for prothrombin time (PT), activated partial thromboplastin time (aPTT) and fibrinogen assays. In 2020, we carried out a cross-sectional study at the transfusion centre of Ouagadougou and included 280 healthy blood donors (140 males and 140 females) as reference subjects (RS) according to CLSI guidelines (C28 A3). From each RS a 5 mL blood sample had been withdrawn in citrated tubes. We performed PT, aPTT and fibrinogen assays using the Sysmex™ CA660 coagulometer and Siemens™ reagents. RV were calculated using the "central 95 percentile" method. Reference values of PT, aPTT and Fibrinogen were respectively [73.84%-117.50%], [20,01-29.45] seconds and [2.04-3.83] g/L for females and [58.81%-112,31%] seconds, [20,9-29,98] seconds and [1.58-3.35] g/L for males. We report for the first time locally appropriate haemostasis RV for the Burkina Faso adult's population. They will be of clinical use to our health care professionals.The ordering of clinical haemostasis tests is increasing in Burkina Faso due to the newly emergence of cardiovascular and metabolic diseases. However, appropriate local reference values (RV) are lacking. Our study aimed to establish RV for prothrombin time (PT), activated partial thromboplastin time (aPTT) and fibrinogen assays. In 2020, we carried out a cross-sectional study at the transfusion centre of Ouagadougou and included 280 healthy blood donors (140 males and 140 females) as reference subjects (RS) according to CLSI guidelines (C28 A3). From each RS a 5 mL blood sample had been withdrawn in citrated tubes. We performed PT, aPTT and fibrinogen assays using the Sysmex™ CA660 coagulometer and Siemens™ reagents. RV were calculated using the "central 95 percentile" method. Reference values of PT, aPTT and Fibrinogen were respectively [73.84%-117.50%], [20,01-29.45] seconds and [2.04-3.83] g/L for females and [58.81%-112,31%] seconds, [20,9-29,98] seconds and [1.58-3.35] g/L for males. We report for the first time locally appropriate haemostasis RV for the Burkina Faso adult's population. They will be of clinical use to our health care professionals.